Influence of different types of solvent on the effectiveness of nanolime treatments on highly porous mortar substrates. (10th January 2020) - Otero, J.; Starinieri, V.; Charola, A.E.; Taglieri, G.
Highlights: Nanolime in water presents a better-defined crystalline structure after carbonation. Nanolime dispersed in WIP solvent presents a more homogeneous penetration. Treatments of nanolime in water and WIP present higher consolidating properties. All nanolime treatments produced an undesired whitening of the substrate's surface. Abstract: Historic calcareous structures suffer from weathering processes that result in the loss of some of their original properties. Nanolime products represent an attractive choice for the consolidation of these substrates containing calcite due to their high chemical compatibility with the original structure. The effectiveness of nanolime products has been widely proven for superficial consolidation treatments (e.g. plasters and wall-paintings). However, its consolidation mechanism in highly porous substrates (e.g. limestones or lime mortars) still needs to be fully understood. The aim of this paper is to study the influence of different types of solvent on the effectiveness of nanolime treatments on highly porous lime-mortars. The consolidation effectiveness is investigated by evaluating changes on superficial cohesion, porosity, drilling resistance, water absorption by capillarity, drying rate and aesthetic properties. Results showed that nanolime dispersed in a mixture of isopropanol (50%) and water (50%) yielded slightly better consolidation properties in terms of reduction in porosity, increase in strength and penetration within coarse lime-mortars than nanolime dispersed in other solvents.